2018
DOI: 10.1186/s12985-018-1023-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of enterovirus 71 replication and viral 3C protease by quercetin

Abstract: BackgroundEnterovirus 71 (EV71) is one of the major causative agents of hand, foot, and mouth disease (HFMD), which is sometimes associated with severe central nervous system disease in children. There is currently no specific medication for EV71 infection. Quercetin, one of the most widely distributed flavonoids in plants, has been demonstrated to inhibit various viral infections. However, investigation of the anti-EV71 mechanism has not been reported to date.MethodsThe anti-EV71 activity of quercetin was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 46 publications
3
63
0
2
Order By: Relevance
“…Quercetin was also investigated for its anti-apoptotic potential against virus-induced cell death. Quercetin was able to prevent the viral spread induced by apoptosis, thus making it a dual action antiviral agent [82].…”
Section: Quercetin and Its Derivativesmentioning
confidence: 99%
“…Quercetin was also investigated for its anti-apoptotic potential against virus-induced cell death. Quercetin was able to prevent the viral spread induced by apoptosis, thus making it a dual action antiviral agent [82].…”
Section: Quercetin and Its Derivativesmentioning
confidence: 99%
“…Our results suggest that Cur‐CQDs‐180 can inhibit ROS formation and the resultant p38 kinase activation induced by EV71, which agrees with the reports that highly antioxidative polyphenols, flavonoids, and terpenoids mediated to alleviate enterovirus infections . A further report indicated that natural compounds with high ROS scavenging activity could inhibit EV71‐induced cyclooxygenase‐2 (COX‐2) expression and regulate prostaglandin E‐2 (PGE 2 ) release by activating multiple inflammatory signaling pathways . PGE 2 plays a central role in inflammatory responses, and COX is the rate‐limiting enzyme that governs the first two steps in the synthesis of PGE 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin can reduce the apoptosis rate of rat alveolar cells and inhibit in ammation by suppressing the expression of TGF-β1, TNF-α and so on [12]. In addition, studies have shown that quercetin also has a great diversity of pharmacological activities like antioxidation [13][14][15], antitumor [16][17][18][19], antiviral [20][21][22][23] and immunoregulation [24][25][26]. The pharmacological effects of irisolidone include anti-in ammatory, antioxidation, antibacterial and antitumor impacts [27].…”
Section: Discussionmentioning
confidence: 99%